POTRET DAKWAH ISLAM DI INDONESIA: STRATEGI DAKWAH PADA ORGANISASI WAHDAH ISLAMIYAH DI KOTA GORONTALO - Dian Adi Perdana; Arianto S Panambang (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2019)
This paper aims to describe the preaching management strategy of the Wahdah Islamiyah organization in Gorontalo City. Besides this paper also looks at the influence of management in the success of the organization to preach. This paper is the result of organizational management research studies based on social religion. In conducting studies, researchers use qualitative types with observation, interview, and documentation techniques. This research was conducted for 23 days in collaboration with a lecturer and student team. The research began with the increasingly well-known Wahdah Islamiyah as an organization in Gorontalo City and had a significant impact on changes in people's behavior, so researchers were interested in examining objects holistically. The results of our research show that Wahdah Islamiyah's preaching strategy through education media, tabligh akbar, environmental and social media. In its development, Wahdah Islamiyah experienced organizational rationalization both in its basic philosophy and organizational processes. Relations and communication patterns become rational. Member participation and contribution changes from "who is mandated" to "who has the opportunity and who is willing". The meaning of the word "participation" changes, Previously participation was a personal demand, then later, participation was an organizational demand. The proof is clear that organizational management steps taken as a preaching strategy that has been taken are Lazis Wahdah, Wahdah Islamiyah Islamic Boarding School, Muslimah Forum and various other institutions that support the development and development of this organization.